First Bis(σ)‐borane Complexes of Group 6 Transition Metals: Experimental and Theoretical Studies. Issue 36 (30th May 2019) - Lenczyk, Carsten; Roy, Dipak Kumar; Ghosh, Bijoy; Schwarzmann, Johannes; Phukan, Ashwini K.; Braunschweig, Holger
Abstract: A series of bis(σ)‐borane complexes of Group 6 transition metals were prepared by direct dihydroborane coordination to the metal center. Reaction of [M(CO)3 (PCy3 )2 ] and two dihydroboranes [DurBH2 ] and [(Me3 Si)2 NBH2 ] (Dur=2, 3, 5, 6‐Me4 C6 H) yielded bis(σ)‐borane complexes fac ‐[M(CO)3 (PCy3 )η 2 ‐(H2 BR)] (R=Dur; 1 : M=Cr, 2 : M=W; R=N(SiMe3 )2 ; 3 : M=Cr, 4 : M=W). In the case of molybdenum, we have isolated an arene complex (5 ) with [DurBH2 ] in which the Dur group acts as a η 6 ‐bound ligand, and with [(Me3 Si)2 NBH2 ] a similar bis(σ)‐borane complex was isolated, cis, trans ‐[Mo(CO)2 (PCy3 )2 η 2 ‐(H2 BN(SiMe3 )2 ] (6 ), with a different pattern of auxiliary ligands. The complexes were investigated by multinuclear NMR spectroscopy, mass spectrometry, X‐ray diffraction analysis, and computational methods. Quantum theory of atoms in molecules (QTAIM) calculations demonstrated that the borane complexes may be described as pure bis(σ)‐borane complexes rather than elongated or stretched examples given that the calculations do not show the presence of a ring‐critical point (RCP) at the ring formed by the interactions of the B−H with metal center. Abstract : Boranes conquer another group : The judicious selection of metal precursors has permitted the isolation of bis(σ)‐borane complexes of Group 6 metals for the first time. Complexes with chromium and tungsten were prepared by direct dihydroborane coordination to the metal center. Calculations demonstrated that the borane complexes may be described as pure bis(σ)‐borane complexes.